The Need To Study Pedagogical Professional Thinking (Eurasian Journal of Learning and Academic Teaching, 2022)
Professional thinking is the sum of individual abilities and personal characteristics, and thinking qualities, which are determined professionally on the basis of a professiogram, the main characteristics of the teacher's professional activity, the abilities of teachers in pedagogical activity that ensure the success of professional pedagogical activity, personal qualities, interests and inclinations are considered important factors in studying the development of professional thinking